Palliative care providers’ use of digital health and perspectives on technological innovation: a national study - Mills, Jason; Fox, Jennifer; Damarell, Raechel; Tieman, Jennifer; Yates, Patsy (BMC palliative care, 2021)
Background While the need for digital health capability and technological innovation in palliative care services is growing rapidly, relatively little is known about the current uptake and views of individual palliative care practitioners. This study aims to explore palliative care practitioners’ current use of and perspectives on digital health innovation in palliative care. Methods A descriptive cross-sectional survey with a web-based questionnaire was used. Participants were multidisciplinary palliative care practitioners in Australia. Results Surveys were returned by 170 medical, nursing, and allied health practitioners working in palliative care. Most respondents reported using a variety of digital health technology associated with clinical information systems, mobile devices, SMS text messaging, teleconferencing, and Wi-Fi. These technologies were used for the purpose of communicating with other health professionals, accessing web-based or mobile health palliative care resources, collecting or managing patient data, and providing information or education. However, few reported electronic access to patients’ advance care planning documentation or could update these data. Respondents were moderately confident in their ability to use digital health, held positive beliefs that palliative care could be enhanced through digital health, and were generally supportive of ongoing innovation through digitally-enable models of care. Palliative care providers would most like to see digital health innovations in the areas of client health records, telehealth, and personal health tracking. Conclusion This is the first national study of digital health in Australian palliative care providers. It contributes new knowledge in this important area of palliative care practice to guide policy and education, whilst informing future directions for research.